Anthropomorphology of the frontal tibial muscle in man's ontogenesis - Kołaczkowski, Zdzisław; Stachura , Danuta (Anthropological Review, 1974)
The frontal tibial muscle of human fetuses in various periods of their development was studied and their distinctive, descriptive as well as metrical characteristics compared.For research work 30 fetuses (17 female and 13 male) were taken. Their crown-rump length (Si) ranged from 170 mm to 380 mm i.e. they were of about 20 - 44 weeks old. The preparations were made with the aid of binoculars that magnified three times. The measurements were taken by means of a movable sliding scale on a vernier. Attention was paid to descripive and metrical characteristics.To make a comparison of measurements obtained from fetuses of various size possible, indices in percentage of the total length of tibia have been calculated.